Pyrone and Unusually Furanone-substituted Flavones from the Leaves of Hoslundia opposita - Salame, Rim; Cheikh-Ali, Zakaria; Bories, Christian; Adiko, Marcelline; Poupon, Erwan; Champy, Pierre (Planta Medica, 2012)
Two new unusual 6-furanoflavones, hoslunfuranine (5) and 5-O-methylhoslunfuranine (6), were isolated from the leaves of Hoslundia opposita Vahl.. Four known methylpyranoflavonic analogues [hosloppin (1), hoslundin (2), 5-O-methylhoslundin (3), oppositin (4)], all specific of the species, were also obtained. Their structures were established on the basis of their spectroscopic data. In vitro cytotoxic, trypanocidal, and leishmanicidal activities of compounds 1 and 3 to 6 were evaluated. Compounds 4 and 6 exhibited leishmanicidal potential in the micromolar range.
Keywords: antiparasitic activity; cytotoxicity; furanoflavones; Hoslundia opposita Vahl.; Lamiaceae